Delimiting the distribution range of Indirana leithii (Boulenger, 1888) (Anura: Ranixalidae), an endemic threatened anuran of the Western Ghats, based on molecular and morphological analysis - Modak, Nikhil; Padhye, Anand; Dahanukar, Neelesh (Zootaxa, 2014)
Indirana leithii (Boulenger, 1888) (Anura: Ranixalidae) is a frog species endemic to the Western Ghats and is categorized as Vulnerable according to IUCN red list. This species is currently considered to be widespread over the entire Western Ghats. Our study based on molecular data (using DNA sequence fragments of the mitochondrial 12S rRNA and 16S rRNA genes and the nuclear rhodopsin gene), morphological analysis of topotypic material as well as material collected from a wide range within the northern Western Ghats, suggests that the species has instead a restricted range in the state of Maharashtra. Specimens identified as I. leithii from the southern Western Ghats as well as from outside the Western Ghats probably belong to hitherto undescribed species. To facilitate future studies in understanding the nature of this species complex and provide better means for identification and delimitation of species we provide molecular, morphological and osteological characters of I. leithii from topotyic material.